2011
DOI: 10.3727/096368911x566217
|View full text |Cite
|
Sign up to set email alerts
|

The Time is Crucial for Ex Vivo Expansion of T Regulatory Cells for Therapy

Abstract: Ex vivo expanded CD4+ CD25 high CD127 − T regulatory cells (Tregs) are recognized as a promising candidate for immunosuppressive therapy in humans. However, due to the plasticity of Tregs lineage and artificial environment present during ex vivo expansion, Tregs easily lose suppressive activity. Here, we followed expanding CD4 + CD25 high CD127 − Tregs and their naive (CD45RA + ) and memory-like (CD45RA − ) subsets in order to establish the best conditions of the expansion. We found that, regardless of the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…The patients administered with two doses of Tregs preserved proportions closest to the baseline ratio. This temporary change was probably mostly caused by the content of the administered expanded Tregs, which are usually Tcm FoxP3 high Tregs [9]. The fact that they reverted to the baseline ratio in treated subjects suggests a possibility that the level and proportions of Tregs, like other lymphocytes, are homeostatically regulated to some ‘baseline’ levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients administered with two doses of Tregs preserved proportions closest to the baseline ratio. This temporary change was probably mostly caused by the content of the administered expanded Tregs, which are usually Tcm FoxP3 high Tregs [9]. The fact that they reverted to the baseline ratio in treated subjects suggests a possibility that the level and proportions of Tregs, like other lymphocytes, are homeostatically regulated to some ‘baseline’ levels.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion was performed under GMP conditions and according to our previously described protocol using anti-CD3/anti-CD28 beads, interleukin 2 (IL-2) and autologous serum. The final product on release kept the FoxP3 expression above 90% [median (min.–max) = 91% (90–97)] [9]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that Treg that remain in ex vivo culture for too long begin losing their characteristic phenotype and function (36). Similarly, it has been shown that too many restimulations decrease Treg suppressive function despite continued expression of Foxp3 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Donor age is only one example of many factors which can affect fold of expansion [10, 25, 26]. Even despite optimized expansion protocol (culture conditions and time), lower starting with numbers of Tregs requires higher fold increase during expansion to generate sufficient final number of Tregs for clinical application, which leads to higher risk of failure [26]. As increasing blood drawing volume to obtain higher starting Treg number is impractical, we decided to utilize leukapheresis for initial Treg cell retrieval.…”
Section: Introductionmentioning
confidence: 99%